2019
DOI: 10.1038/s41467-018-07974-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrotranspositional landscape of Asian rice revealed by 3000 genomes

Abstract: The recent release of genomic sequences for 3000 rice varieties provides access to the genetic diversity at species level for this crop. We take advantage of this resource to unravel some features of the retrotranspositional landscape of rice. We develop software TRACKPOSON specifically for the detection of transposable elements insertion polymorphisms (TIPs) from large datasets. We apply this tool to 32 families of retrotransposons and identify more than 50,000 TIPs in the 3000 rice genomes. Most polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 53 publications
8
121
1
Order By: Relevance
“…Despite a relatively narrow genetic diversity, the 25,000 cultivars grown around the world today exhibit an extraordinary phenotypic diversity and the underlying allelic variants are being progressively identified thanks to the advent of high-throughput genome sequencing. In this context, we show that TIPs, which to date have been ignored from population genomic studies in tomato, are an important diversifying force to consider, as has been proposed for other plant species 27,33,34,[52][53][54][55][56][57] . In particular, most TE insertions are low frequency variants, they are typically not tagged by SNPs, representing a previously uncharacterized source of phenotypic variation.…”
Section: Discussionmentioning
confidence: 78%
“…Despite a relatively narrow genetic diversity, the 25,000 cultivars grown around the world today exhibit an extraordinary phenotypic diversity and the underlying allelic variants are being progressively identified thanks to the advent of high-throughput genome sequencing. In this context, we show that TIPs, which to date have been ignored from population genomic studies in tomato, are an important diversifying force to consider, as has been proposed for other plant species 27,33,34,[52][53][54][55][56][57] . In particular, most TE insertions are low frequency variants, they are typically not tagged by SNPs, representing a previously uncharacterized source of phenotypic variation.…”
Section: Discussionmentioning
confidence: 78%
“…Carpentier et al . () developed a new software package, Trackposon , that was used to identify retrotransposon TIPs among the 3000 rice genomes (Rice genome project, ). This method is a two‐step procedure consisting of first mapping the Illumina reads onto a consensus TE sequence and then mapping the un‐mapped paired reads onto the reference rice genome.…”
Section: Te Activity In Cultivated Ricementioning
confidence: 99%
“…The efficiency of GWAS is such that it is usually able to detect associations between traits and alleles with a minimum allele frequency (MAF) of at least 5% (Willard, 2013). However, the majority of TIPs in rice are found at a much lower frequency (Carpentier et al, 2019). Consequently, we had to adapt our method to this peculiarity of TE insertions.…”
Section: Te-gwasa New Strategy To Unravel the Functional Impact Ofmentioning
confidence: 99%
“…Detailed analyses suggested that there were also examples of gene fragments that had been captured and moved by Helitron transposons (Lai et al ., ; Du et al ., ; Morgante et al ., ). Studies of TE variability in plants on a genome‐wide scale have largely focused on using short‐read resequencing data to map new insertions (Quadrana et al ., ; Carpentier et al ., ; Tian et al ., ; Lai et al ., ; Stuart et al ., ); however, this approach can be complicated by non‐alignable sequences and the repetitive nature of TEs.…”
Section: Introductionmentioning
confidence: 99%